Pengaruh Konflik Audit, Skeptisisme Profesional dan Lowballing Terhadap Ketepatan Pemberian Opini Audit Dengan Etika Auditor Sebagai Variabel Moderasi - Saptaningtyas, Angel; Jasman, Jasman (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of audit conflict, professional skepticism, and lowballing on the accuracy of audit opinion issuance, with auditor ethics as a moderating variable. This study employs a quantitative approach using data collected through a questionnaire distributed to auditors at Public Accounting Firms (PAFs) and analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with the assistance of SmartPLS. The results indicate that audit conflict and professional skepticism have a positive and significant effect on audit opinions, while lowballing has a negative and significant effect on audit opinions. Additionally, auditor ethics also have a positive effect on audit opinions. In the moderation test, auditor ethics were found to significantly moderate the effects of professional skepticism and lowballing on audit opinions, but failed to moderate the effect of audit conflict on audit opinions. These findings indicate that enhancing professional attitudes and the application of sound auditor ethics are crucial for producing high-quality audit opinions; therefore, public accounting firms are expected to strengthen the application of professional ethics and control lowballing practices to maintain audit independence and quality.